Purchase of medications without prescription in Peru: a cross-sectional population-based study - Hernández Vásquez, Akram (2019)
Background: Low availability of medicines in health services, self-medication, inadequate use of medicines, and inadequate dispensing practices in pharmacies are frequent problems in Peru. We aimed to evaluate how frequent the purchase of medications without medical prescription is in Peru, and which factors are associated with this practice. Methods: We conducted a secondary analysis of the 2016 ENSUSALUD national survey data. Purchase of medicines that require a prescription was measured as a dichotomous coded as bought one or more medicines that requires medical prescription or bought medicines that do not require a prescription. Crude and adjusted prevalence ratios (PR) and their 95% confidence intervals (95% CI) were calculated using Poisson regressions model with robust variance to assess the association of purchasing of medicines that require prescriptions with sociodemographic factors. Results: There were 3858 participants in the dataset. The prevalence of purchasing medications without prescriptions was 47.2%. History of having previously consumed the same medication (31.6%), and the delay in receiving an appointment at health facilities (26.9%) were the main reasons to buy medications without a prescription. Regarding the recommendation of the medication purchased, the advice of the pharmacy, and remembering a previous old prescription, were the most frequent reasons (38.3%, and 25.9%, respectively). On the multivariable analysis, users that buy medications without prescription were more likely to be of aged 24-45; reside in the Amazon and Highlands regions; and self-consumption of the purchase. Individuals with Seguro Integral de Salud (Comprehensive Health Insurance) were less likely to buy medications without prescription. Conclusions: There is a high prevalence of prescription requiring medication being bought without one from pharmacies in Peru. It is necessary to include the evaluation of consumer patterns to develop strategies with the aim to regulate the consumption of prescription drugs in the Peruvian population.